Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) = 9x2 - ( y2 - 10y + 25y2 ) = ( 3x )2 - ( y - 5 )2 = ( 3x - y + 5 )( 3x + y - 5 )
b) = ( x3 - 8 ) - ( x2 - 4x + 4 ) = ( x - 2 )( x2 + 2x + 4 ) - ( x - 2 )2 = ( x - 2 )( x2 + x + 6 )
c) = ( 4a2 - 4a + 1 ) - ( b2 - 2bc + c2 ) = ( 2a - 1 )2 - ( b - c )2 = ( 2a - b + c - 1 )( 2a + b - c - 1 )
d) = ( a3 + 3a2 + 3a + 1 ) - 27b3 = ( a + 1 )3 - ( 3b )3 = ( a - 3b + 1 )( a2 + 9b2 + 3ab + 3b )
a. \(9x^2-\left(y^2-10y+25\right)=9x^2-\left(y-5\right)^2=\left(3x-y+5\right)\left(3x+y-5\right)\)
b.\(x^3-8-x^2+4x-4=\left(x-2\right)\left(x^2+2x+4\right)-\left(x-2\right)^2=\left(x-2\right)\left(x^2+x+6\right)\)
c.\(\left(4a^2-4a+1\right)-\left(b^2-2bc+c^2\right)=\left(2a-1\right)^2-\left(b-c\right)^2=\left(2a-1+b-c\right)\left(2a-1-b+c\right)\)
d.\(\left(a^3+3a^2+3a+1\right)-27b^3=\left(a+1\right)^3-\left(3b\right)^3=\left(a+1-3b\right)\left[\left(a+1\right)^2+3b\left(a+1\right)+9b^2\right]\)
Ta có:
\(VT=\left[\dfrac{16a-a^2-\left(3+2a\right)\left(a+2\right)-\left(2-3a\right)\left(a-2\right)}{\left(a-2\right)\left(a+2\right)}\right]:\dfrac{a-1}{a^3+4a^2+4a}\)
\(=\dfrac{16a-a^2-3a-6-2a^2-4a-2a+4+3a^2-6a}{\left(a-2\right)\left(a+2\right)}.\dfrac{a\left(a+2\right)^2}{a-1}\)
\(=\dfrac{a-2}{\left(a-2\right)\left(a+2\right)}.\dfrac{a\left(a+2\right)^2}{a-1}=\dfrac{a\left(a+2\right)}{a-1}\left(a\ne\pm2;a\ne1\right)\)
\(=a-\dfrac{a\left(a+2\right)}{a-1}=\dfrac{a^2-a-a^2-2a}{-1}=\dfrac{-3a}{a-1}=\dfrac{3a}{1-a}=VP\left(đpcm\right)\)
a: a<b
nên 3a<3b
=>3a-1<3b-1
=>3a-1<3b+1
b: a<b
nên -4a>-4b
=>-4a-2>-4b-2
=>-4a-2>-4b-3
\(\left(4a^2-3a-18\right)^2-\left(4a+3a\right)^2\)
\(=\left(4a^2-3a-18-4a^2-3a\right)\left(4a^2-3a-18+4a^2+3a\right)\)
\(=\left(-6a-18\right)\left(8a^2-18\right)\)
\(\left(4a+2\right)\left(-3a+1\right)\)
\(=-12a^2+4a-6a-2\)
\(=-12a^2-2x-2\)
Sửa dòng cuối giúp mình thành:
\(=-12a^2-2a+2\)